The bickering brethren: Malaysia-Brunei Territorial Disputes 2003-2009 and Their Resolutions / Khairun Syazwan Maharup ... [et al.] - Maharup, Khairun Syazwan; Ayob, Azman; Chandran, Suseela Devi; Mahamad Aziz, Farhatul Mustamirrah (2021)
Malaysia's territorial disputes in the South China Sea are shared with many other claimants. Among the territorial disputes occurred between Malaysia and other members of the Association of Southeast Asian Nation (ASEAN) are Indonesia over Sipadan - Ligitan Islands, Singapore over Batu Puteh Island, the Philippines and Vietnam over the Spratly Islands and Brunei over Lawas, Limbang, Terusan, Rangau and Louisa Reef (Terumbu Semarang Barat Kecil) (Asri, 2016). About this dispute, there were several methods that Malaysia decided to employ. For example, Malaysia engaged with the International Court of Justice (ICJ) to solve the Batu Puteh dispute with Singapore. However, in the disputes with Brunei, Malaysia rejected the idea of using ICJ to solve the issue. This shows that Malaysia and Brunei opted to use peaceful settlement which is in line with the principle of ASEAN and a good foreign policy approach through dialogues to achieve a peaceful resolution that benefited both countries' national interests. In Malaysia and Brunei territorial disputes, a few issues had arisen. One of the issues was about the Limbang status claimed by Brunei. The former Malaysian Prime Minister, Dr. Mahathir Mohamad queried about the loss of USD 100 billion of Malaysia's oil in the deal with Brunei to get back Limbang during Abdullah Ahmad Badawi's administration as the Prime Minister. Dr. Mahathir continued to comment on how Abdullah Badawi's government had negotiated with the Sultan of Brunei to drop his claim of Limbang, Sarawak which involved the exchange of two newly discovered oil blocks. Dr. Mahathir also believed that the two oil blocks are no longer parts of Malaysia even though Malaysia has the right to claim the two blocks based on historical facts ("Mahathir Queries Loss of USD 100 Billion", 2010). The purpose of this paper is to explain the current territorial disputes that occurred between Malaysian and Brunei between 2003 and 2009. This paper also highlights which territories that were in dispute between the two countries, the reason behind these conflicts, and resolutions taken by Malaysia and Brunei.